Antecedentes histórico-filosóficos da problemática do tempo e do mal no Freiheitsschrift de Schelling: aproximações gnósticas - Fernandes, Edrisi de Araújo (2010)
This thesis aims better understanding the relation between time and evil in Schelling s Freiheitsschrift, having its starting point in approximations from Gnosticism. For that purpose, before approaching that relation, it is reviewed (chapter I) the question of Gnosticism, a strain of thought essentially concerned with the problem of time and permeated by the belief in an evil nature of creation, and which is alleged to have significantly influenced certain ideas of Schelling. An evaluation of approximations between Gnosticism, gnosis and German thought follows (chapter II), as well as an evaluation of Schellingian aproximations to Gnosticism (chapter III). Then, the Freiheitsschrift is analysed as the text where Schelling, having taken hold of a very distinct appropriation of Gnosticism, goes beyond Kantian theodicy (chapter IV). Some interrogations about whether key ideas of Schellingian philosophy (about gnosis, creation, duality, time, and evil) are conceived in a way that is essentially different from that of historic Gnosticism, despite the much that has been said to the contrary, are then addressed (chapter V). The proposal of a Platonic-Plotinian key to the understanding of the relations between time and evil in the Freiheitsschrift comes next (chapter VI), and then gives way to the concluding remarks (chapter VII). We perceive that Gnosticism and Neoplatonism are systems of thought that sometimes converge, and that German thought is one of the places of this convergence. Notwithstanding this perception, it is possible to affirm that Schellingian thought, with its valorization of time and of a certain perception of evil, is essentially anti-gnostic, despite some contrary observations